Cover Picture: One‐For‐All Polyolefin Functionalization: Active Ester as Gateway to Combine Insertion Polymerization with ROP, NMP, and RAFT (Angew. Chem. Int. Ed. 33/2022). Issue 33 (1st August 2022) - Dau, Huong; Tsogtgerel, Enkhjargal; Matyjaszewski, Krzysztof; Harth, Eva
Abstract : A polyolefin active ester exchange (PACE) process was developed for polyolefin‐containing block copolymer synthesis and serves as a bridge connecting coordination–insertion polymerization to multiple controlled polymerization methods. As reported by Krzysztof Matyjaszewski, Eva Harth et al. in their Research Article (e202205931 ), PACE allows for the synthesis of hybrid materials that comprise olefins and ester, styrene, vinylic, acrylate, and acrylamide segments with a broad window for tunability. Nano‐objects with higher‐order morphologies can be obtained directly via RAFT‐mediated PISA.